2023
DOI: 10.3390/electronics12132964
|View full text |Cite
|
Sign up to set email alerts
|

LiNbO3 Surface Acoustic Wave Resonators with Large Effective Electromechanical Coupling

Abstract: This paper reports an LNO surface acoustic wave (SAW) resonator based on a shear horizontal mode with high operating frequency over 3 GHz, large electromechanical coupling of 33.54%, Q factor of 380, and a relatively good figure of merit (FOM) of 127. Combing crystal-ion-slicing (CIS) technology with a room temperature bonding method, a 4-inch single crystalline LNO thin film on silicon is prepared successfully. The influence of damaged LNO film on crystalline quality and SAW performance is comprehensively ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This property is useful, e.g., for surface acoustic wave devices in signal processing. 9 These materials also have interesting piezoelectric properties for applications as sensors and actuators. 10,11 Finally, this class of materials is of interest for nanoelectronics due to metallic-like conductivity at charged domain walls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This property is useful, e.g., for surface acoustic wave devices in signal processing. 9 These materials also have interesting piezoelectric properties for applications as sensors and actuators. 10,11 Finally, this class of materials is of interest for nanoelectronics due to metallic-like conductivity at charged domain walls.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the ferroelectric state gives rise to a high spontaneous electric polarization below the Curie temperature, which can be influenced by external electric fields. This property is useful, e.g., for surface acoustic wave devices in signal processing . These materials also have interesting piezoelectric properties for applications as sensors and actuators. , Finally, this class of materials is of interest for nanoelectronics due to metallic-like conductivity at charged domain walls. High-quality single crystals necessary for device building are commonly produced by the Czochralski method, resulting in a congruent composition of about 48.6 mol % Li 2 O …”
Section: Introductionmentioning
confidence: 99%
“…25 The research has mainly explored the influence of different crystal structure doping on the characteristics of LiNbO 3 , attempting to apply it to sensing detection in pressure, 26 temperature, 27 and electromagnetic fields. 28 Due to the excellent optical performance of LiNbO 3 , it is now widely used in resonators, 29 optical modulators, 30 and integrated optical devices. 31 Zhang et al reported a non-metallic structure Ti∶LiNbO 3 optical waveguide high electric field sensor.…”
Section: Introductionmentioning
confidence: 99%